Desenvolvimento de uma nova técnica para identificação de faltas de alta impedância através da análise do campo magnético dos alimentadores de distribuição - Paula, Vinicius Cardoso de (2018)
This work presents a non-intrusive method for detecting high-impedance faults in power distribution systems. Such method consists of measuring and analyzing the magnetic flux density generated by grid conductors by utilizing a system composed by a coil, a voltage signal conditioning circuit and an Arduino microcontroller. The analysis of the signal is done by monitoring the amplitudes of inter-harmonic components in the vicinity of the fundamental component. The results show that the use of contactless indirect current measurement system can be quite effective when it comes to detecting these faults.